Strengthening Islamic Religious Education And Character Education For Children In Pasir Putih Hamlet, Dwi Karya Bakti Village, Pelepat Subdistrict, Bungo Regency, Jambi Province - Mahluddin Mahluddin; Dian Nisa Istofa (Abdimas Indonesian Journal, 2026)
This program aims to strengthen Islamic education and character education among the Anak Dalam tribe. Researchers observed in the field that there are differences in the beliefs of the Anak Dalam tribe (SAD) living in Pasir Putih Village, Pelepat Subdistrict, Bungo Regency, Jambi. This empowerment initiative employs the PAR (Participatory Action Research) method. This method fosters an understanding and awareness that enables the community to transform their own circumstances through their own efforts, rather than in response to directives from outside parties. The PAR cycle begins with problem identification, potential identification, action planning, and reflective evaluation. This community empowerment process involves stakeholders from the planning stage through action and evaluation, with the following empowerment steps: First, the Pre-Mentoring Process, which was already carried out during the implementation of the 2019 UIN Jambi Student Community Service (KKN) Research Action Program; this stage involves identifying problems occurring at the research site. Second, the Acculturation Process, which involves mapping the SAD community—which adheres to two religious beliefs—as well as observing and adapting to the activities carried out by the SAD community, with the aim of fostering good communication between researchers and the SAD community. Third, the First Action Program, which involves developing learning modules and simultaneously providing guidance to SAD children. Fourth, the Evaluation Program was conducted to assess the effectiveness of the mentoring provided and the SAD children’s mastery of Islamic religious education and character education. The research findings indicate that despite differences in religious beliefs, SAD children are enthusiastic about learning about Islam and character education. Challenges in implementation include a shortage of educators and a lack of adequate educational resources.